Updates in the Management of ARDS - Nichols, Emma Hitt (MD Conference Express, 2014)
Acute respiratory distress syndrome (ARDS) causes substantial morbidity and mortality in patients in the intensive care unit; the only clinical intervention that has demonstrated efficacy in patients with ARDS has been lung protective ventilation. This article discusses various studies, analyses of admissions, and surveys completed by physicians.